Annotated Southern Ocean diatom LM micrographs from Polarstern cruises PS79 & PS103 - Michael Kloster; Bánk Beszteri; Tim W Nattkemper (PANGAEA, 2024)
Several sets of annotated (taxon, expedition, station) high resolution focus-enhanced light micoscopy images depicting valves of the Southern Ocean diatom species and genera Fragilariopsis kerguelensis, Pseudonitzschia, Chaetoceros, Thalassiosira lentiginosa, Fragilariopsis rhombica, Rhizosolenia, Asteromphalus, Thalassiosira gracilis and Nitzschia, plus the non-diatom taxon silicoflagellates. Objects are imaged with and without background masking. Pixel size is 0.098 x 0.098 μm^2.